2015
DOI: 10.1111/ggi.12537
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to low serum vitamin B12 levels in elderly patients with non‐atrophic gastritis in contrast to patients with normal vitamin B12 levels

Abstract: Helicobacter pylori was present significantly more often in older patients whose serum vitamin B12 levels were ≤200 pg/mL, and Helicobacter pylori density was inversely correlated with serum B12 level. Upper gastrointestinal endoscopic examination should be suggested for elderly patients with serum vitamin B12 level ≤200 pg/mL. Geriatr Gerontol Int 2015; ●●: ●●-●●.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…also demonstrated an association between copper levels and high titers of anti‐ H. pylori IgA in patients with IDA, possibly playing a role in the disease. As reported by Kalkan et al, H. pylori infection may be more often diagnosed in older patients whose serum vitamin B12 levels were 200 pg/mL; moreover, the same levels show an inverse relation with H. pylori density …”
Section: Hematologic Diseasesmentioning
confidence: 61%
“…also demonstrated an association between copper levels and high titers of anti‐ H. pylori IgA in patients with IDA, possibly playing a role in the disease. As reported by Kalkan et al, H. pylori infection may be more often diagnosed in older patients whose serum vitamin B12 levels were 200 pg/mL; moreover, the same levels show an inverse relation with H. pylori density …”
Section: Hematologic Diseasesmentioning
confidence: 61%
“…First, H. pylori infection may lead to systemic inflammation, and release of cytokines, such as TNF-α, IL-1 and IL-6,45 which may cause bone turnover indirectly. Second, many studies have shown that low vitamin B12 may be associated with H. pylori infection 46. If the serum vitamin B12 levels are decreased, the folate becomes trapped as methyltetrahydrofolate and interrupts for folate-related DNA synthesis, which is an important factor for bone remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…The hypochlorhydric stomach affects calcium absorption, calcium homeostasis and bone mass [ 17 ]. In addition, the low serum vitamin B12 level was found in the patients with H. pylori infection [ 18 ]. If the serum vitamin B12 levels are low, the folate becomes trapped as methyltetrahydrofolate and then interrupts for folate-related DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%